Comparison of Pollen Abortiveness in Four Weed Species Treated with Mercuric Chloride - Regis, Emelina; Lagunzad, Daniel (Science Diliman: A Journal of Pure and Applied Sciences; Vol 14 No 1 (2002), 2007)
Pollen grain abortiveness due to mercury exposure was investigated in four species of weeds, namely Cleome rutidosperma Mart., Conmelina diffusa Burm.f., Ludwigia micrantha (L.) Hara, and Stachytarpheta jamicensis (L.) Vahl. All four species tested showed mean pollen grain abortion rates significantly higher than those of their unexposed cohorts. Phollen grain abortion was manifested by reduced size and staining deficiencies. Scheffe’s test for variability indicated that higher mercury concentrations are required to effect changes in pollen grain abortiveness. The weed species tested can possibly be used as bioindicators of mercury pollution. Because of the plant’s ability to absorb mercury, these species can also be considered as possible bioremediators.
Keywords: Pollen abortiveness, Mercury, Bioinidcator, Cleome rutidosperma, Commelina diffusa, Stachytarpheta jamicensis, Ludwigia micrantha